PENGARUH HUTANG, PROFITABILITAS, DAN TANGGUNG JAWAB LINGKUNGAN PADA CSR DISCLOSURE PERUSAHAAN PERTAMBANGAN - Fibrianti, Ni Putu Emmy; Wisada, I Gede Supartha (E-Jurnal Akuntansi; Vol 11 No 2 (2015), 2015)
Corporate social responsibility disclosure has become a matter of disclosure required in Indonesia since the issuance of Undang-Undang No. 40 Perseroan terbatas. This study was conducted to determine the effect of the debt, profitability, and environmental responsibility in the mining company's CSR disclosure. Based on purposive sampling method obtained 10 samples of research that mining companies listed on the Stock Exchange 2011-2013.The analysis technique used is panel data regression model with the Random Effect Model. The results showed that the debt and profitability variables affect the company's CSR disclosure.
Keywords: corporate social responsibility disclosure, PROPER, panel data regression